Targeting Skin Aging: Development of a Phytosomal Polyherbal Gel - G. Sirisha Chowdary (Asian Journal of Pharmaceutics (AJP), 2025)
Ageing is a biological process that involves a multitude of external and internal factors, such as genetic and environmental influences, and induces characteristic molecular, cellular, tissular, and clinical changes. Antiaging drugs are mainly responsible for free radical scavenging, supplying vitamin C, suppressing the production of melanin, antioxidant activity, and promoting tissue regeneration. The objective of the present study was to prepare the polyherbal antiaging phytosomal gel. Materials and Methods: This formulation hopes for a stable and functionally effective gel and to evaluate for good product performance of the prepared gel. Phytosomes were prepared with active ingredients, such as Eucalyptus globules extract, Clitoria ternatea extract, Annona squamosa extract, Coriandrum sativum extract, and Aloe vera extract. Physical evaluation, such as pH, viscosity, homogeneity, spreadability, extrudability, characterization of phytosomal gel, stability studies, and in vitro antioxidant activity of the antiaging gel was carried out. Results and Discussion: These studies suggest that the composition of extracts and base of gel F3 is more stable and efficient, while the remaining formulations were not stable and resulted in the breakdown of the emulsion when stored for a long time. This formulation had a suitable pH, was homogeneous, emollient, non-greasy, and was easily removed after the application. Conclusion: In this study, the scavenging activity of the F3 sample was found to be dose-dependent.